RENCANA BISNIS PDAM KABUPATEN LOMBOK TIMUR 2021-2026 - LALU MUH. KABUL (Universitas Mahasaraswati K. Mataram, 2023)
The focus of the study is business plan of Regional Drinking Water Company (PDAM) East Lombok Regency 2021-2026 . The study method used is mixed methods, namely quantitative and qualitative. The result of study showed that vision of PDAM is tobe “Health” company and toward excellent service and self relience. In order to achieve the vision, there are 4 missions, objectives, strategy and its performance indicator. Performance indicator of PDAM based BPPSPAM category during periode 2021-2026 is targeted “Health”. Mean while, performance indicator of PDAM based on Kepmendagri Nomor 47 Tahun 1999 category is targeted “Enough